(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
The paper demonstrates the viability of a number of storage techniques such as hashing using multilingual texts. The empirical studies of hashing techniques based on multilingual provide researchers with insight information into the structure of the methods and their applicability. This may lead to more theoretical findings to enhancing performance of storage and retrieval algorithms. A number of experiments were performed using real and random texts from English and Arabic languages with numerous sets of data items and length sizes. The English language is used in the experiments as measurement tools as it is the international language of the world and it has been received the best attention from researchers all over the world. The study shows that chaining techniques consistently generates less number of collisions than open addressing techniques for texts from any language. The motivation behind conducting this study was the lack of research on the performance of hashing algorithms using data items that have dependencies and structures from other than English language. There are also no comprehensive studies performed on Arabic strings. The new finding probably leads to design more efficient hashing algorithms for storing, deleting and retrieving items of information.